SAT0606 The Comorbidity between Systemic Lupus Erythematosus and Malignancies: A Cross-Sectional Population Based Study. (15th July 2016) - Azrielant, S.; Tiosano, S.; Mahroum, N.; Comaneshter, D.; Cohen, A.D.; Amital, H.
Abstract : Background: Autoimmune conditions often reflect dysregulation of the immune system, which appears to be of great significance in the development of malignancies [1]. Previous studies support an association between systemic lupus erythematosus (SLE) and malignancies; however, their findings on specific malignancies are inconsistent, and their design might not represent the population of SLE patients, due to selection bias [2–4]. Objectives: Our goal was to investigate the association between the presence of SLE and various malignancies, in a large-scale population-based study. Methods: Data for this study was collected from the database of "Clalit Health services", the largest state-mandated health service organization in Israel. All adult members diagnosed with SLE were included (n=5, 018) and their age and sex-matched controls (n=25, 090), creating a cross-sectional population-based study. Medical records of all subjects were analyzed for documentation of malignancies. Logistic regression was preformed to control for age, gender, BMI, smoking and socioeconomic status. Results: Diagnosis of malignancy (of any type) was more prevalent in the SLE population in comparison to controls (odds ratio [OR] 3.35, 95% confidence interval [CI] 3.02–3.72). Also, SLE diagnosis was found to be independently associated with higher proportions of non-Hodgkin lymphoma (OR 3.02, 95% CI 2.72–3.33), Hodgkin lymphoma (OR 2.43 95% CI 1.88–2.99), multiple myeloma (OR 2.57, 95% CI 1.85–3.28), cervix uteri malignancies (OR 1.65, 95% CI 1.10–2.20) and genital organ malignancies (OR 2.32 95% CI 1.42–3.22), after adjustment for confounding variables. Conclusions: SLE diagnosis was found to be independently associated with higher proportions of malignancies, specifically hematologic malignancies. These findings should be considered when treating SLE patients, and possibly influence their screening routine. References: de Visser KE, Eichten A, Coussens LM. Paradoxical roles of the immune system during cancer development. Nat Rev Cancer 2006;6:24–37. doi:10.1038/nrc1782 Bernatsky S, Boivin JF, Joseph L, et al. An international cohort study of cancer in systemic lupus erythematosus. Arthritis Rheum 2005;52:1481–90. doi:10.1002/art.21029 Sultan SM, Ioannou Y, Isenberg D a. Is there an association of malignancy with systemic lupus erythematosus? An analysis of 276 patients under long-term review. Rheumatology (Oxford) 2000;39:1147–52. Mellemkjaer L, Andersen V, Linet MS, et al. Non-Hodgkin's lymphoma and other cancers among a cohort of patients with systemic lupus erythematosus. Arthritis Rheum 1997;40:761–8. Disclosure of Interest: None declared